Hyperinflation potential in commodity-currency trading systems: Implications for sustainable development - Yorgos D. Marinakis; Reilly White (Sustainable Technology and Entrepreneurship, 2022)
Sustainable Development implies slowing the rate of utilization and eventual depletion of non-renewable resources such as oil and metals. Non-renewable resources are now commonly traded, often as derivatives, through electronic trading exchanges and studies the impact of that trading on sustainable development are underrepresented. Commodity-currency research since 2003 to some extent has focused on the relationship between commodity prices – including non-renewable resources – and the exchange rates of the currencies of the nations that are extracting those commodities. To a lesser extent, other research on non-renewable resource development has focused on technology and innovation. Here we address one issue at the core of non-renewable sustainable development: the question of commodity-currency linkages and spillovers and their effects on price stability. Our research tool is an economic interpretation of the Lotka-Volterra equations. Using Lotka-Volterra parameters from the fit to actual CAD XCT data, we find that carrying out the currency-commodity dynamics over several centuries demonstrates the possibility for cyclical unsustainable hyperinflation. Devaluing or inflating the currencies or commodities is not a solution to hyperinflation. The solution to hyperinflation is to increase β (the effect of the commodity on the currency) and/or δ (the price decrease rate of the commodity when the currency is absent) and/or decrease γ (the inflation rate of the commodity in the presence of the currency).